2019
DOI: 10.3847/2041-8213/ab1fe6
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Electron Heating by Tangential Discontinuity in the Turbulent Magnetosheath

Abstract: Energetic electrons exist widely in the turbulent magnetosheath, but how they are generated remains unclear. Here we report a new structure, at which electrons are efficiently accelerated in the direction parallel to the magnetic field. Such a structure, formed at the edge of a high-speed jet (HSJ), is a tangential discontinuity (TD) in the MHD regime, but exhibits impulsive fine structures in the kinetic-scale regime. The pulsation of the TD, caused by time-varying size of the HSJ, leads to the energization p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 71 publications
0
31
0
Order By: Relevance
“…The rotational and tangential discontinuities (RDs & TDs) are the most common types observed in the solar wind (Smith 1973;Mariani et al 1983;Paschmann et al 2013). TDs can be treated as stationary boundaries in the plasma rest frame separating distinct plasmas (Burlaga & Ness 1969;Liu et al 2019;Fu et al 2012). RDs, however, are propagating kinks in the magnetic and flow fields (Smith 1973).…”
Section: Introductionmentioning
confidence: 99%
“…The rotational and tangential discontinuities (RDs & TDs) are the most common types observed in the solar wind (Smith 1973;Mariani et al 1983;Paschmann et al 2013). TDs can be treated as stationary boundaries in the plasma rest frame separating distinct plasmas (Burlaga & Ness 1969;Liu et al 2019;Fu et al 2012). RDs, however, are propagating kinks in the magnetic and flow fields (Smith 1973).…”
Section: Introductionmentioning
confidence: 99%
“…In near-Earth space the most important examples are jets generated in the magnetopause and magnetotail current sheets as well as jets downstream of the shock. As jets propagate and interact with the ambient plasma, particles are heated and accelerated at the jet boundary, often referred to as plasma jet front [8,44,[132][133][134][135]. Jets eventually stop in the jet braking regions upon interaction with obstacles, such as the Earth's magnetic dipolar field [136,137], where particles can be efficiently accelerated [138,139] and later injected into the inner magnetosphere [140].…”
Section: How Are Particles Energized In Plasma Jets?mentioning
confidence: 99%
“…As jets propagate in the magnetosheath, they interact with and modify the ambient plasma [155,156]. This interaction creates sites where particles can be efficiently energized, such as magnetic bottles where Fermi acceleration operates [135] and kinetic-scale current sheets [157] and shocks [158]. All these sites have a nonlinear and nonstationary structure whose spatial and temporal evolution cannot be resolved with current four-point measurements even at one given scale.…”
Section: Particle Energization In Magnetosheath Jetsmentioning
confidence: 99%
“…Later, the electron‐scale magnetic holes (ESMHs), whose sizes are less than or of the order of ion gyroradius or ion inertial length, are reported in both observations (Ge et al, 2011; Gershman et al, 2016; Goodrich et al, 2016; Huang, Du, et al, 2017; Huang, Sahraoui, et al, 2017; Huang et al, 2018, 2019; Y. Y. Liu, Fu, Liu, et al, 2019; H. Liu, Zong, Zhang, et al, 2019; Shustov et al, 2019; Yao et al, 2016, 2017) and particle‐in‐cell (PIC) simulations (Haynes et al, 2015; Roytershteyn et al, 2015). The PIC simulation shows that ESMHs can form in decaying turbulent plasmas, and their formation is due to the vortices of trapped electrons with petal‐like orbits (Haynes et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Magnetic holes (MHs), sometimes also referred to as magnetic depressions (MDs) or magnetic cavities, are characterized by the depressions of magnetic field magnitude. Such structures are first reported by Turner et al (1977) in the solar wind and then widely observed in the interplanetary space (Xiao et al, 2014, 2010; Zhang et al, 2008, 2009), the magnetosphere of comet (Russell et al, 1987), and the terrestrial magnetosheath/plasma sheet (Balikhin et al, 2012; Fu, Zhao et al, 2020; Joy et al, 2006; Y. Y. Liu, Fu, Liu, et al, 2019; Lucek et al, 1999; Nowada et al, 2009; Shi et al, 2009; Soucek et al, 2008; Sun et al, 2012; Tsurutani et al, 1982; Zhima et al, 2015). The spatial scales of MHs range from several to thousands of proton gyroradii ρ i (Tsurutani et al, 2011).…”
Section: Introductionmentioning
confidence: 98%